Essentials of intellectual disability assessment and identification : a field guide for applied research - Brue, Alan W.; Wilmshurst, Linda (Essentials of psychological assessment, 2016)
"A concise, up-to-date overview of intellectual disability evaluation and assessment Essentials of Intellectual Disability Assessment and Identification offers a practical, concise overview of the nature of intellectual disability and adaptive skills functioning in children, adolescents, and adults. Coverage includes the latest information on prevalence, causes, differential diagnoses, behavioral and social concerns, test instruments, and the new DSM-5 diagnostic criteria. The discussion promotes a deeper understanding of the use of assessment data to inform interventions in clinical practice. Designed for easy navigation, each chapter highlights important points and key cautions to allow quick reference without sacrificing depth. A sample assessment report illustrates how findings should be communicated to better inform treatment, giving you a practical reference to ensure comprehensive reporting. In 2013, the DSM-5 conceptualization of intellectual disabilities was significantly changed. It's important for professionals to have access to the most current guidelines from a variety of sources, and this book compiles them all into a single reference. Understand the goals of assessment in terms of treatment and intervention Delve into the legal issues resulting from the changes in diagnostic criteria Provide feedback to parents and caregivers of intellectually disabled individuals Learn the unique clinical applications of each assessment instrument Understanding which test to use is not enough; students and professionals need a more comprehensive view of intellectual disabilities, informed by the most up-to-date body of knowledge available. Essentials of Intellectual Disability Assessment and Identification gives you the knowledge base and skill set you need for effective evaluation and assessment"--